Enhancing Construction Worker Safety: Real-time Health Monitoring through Wearable Technology - Lee, Poizot Li (International Enterprise Integration Association, 2023)
Wearable technology can improve worker safety, productivity, and well-being in the construction business, according to this study. Wearable device health parameters are analyzed quantitatively and worker experiences and perceptions are analyzed qualitatively in the study. A paradigm change in construction worker health monitoring is real-time monitoring of important health parameters including heart rate, body temperature, and hazardous exposure with wearable technology. Continuous monitoring allows workers and management to quickly identify and mitigate health risks, creating a safer workplace. Data shows wearable technology's many benefits. Over and above safety, the technology promotes health by giving workers individualized input to make informed health decisions. Management can optimize work conditions, allocate resources, and improve safety standards via data-driven decision-making. Technology adoption issues like privacy and user approval are important. Successful integration into the construction workplace requires ethical practices and user-centric design. This study shows that wearable technologies can transform construction worker health monitoring. The study's findings inspire innovation, interdisciplinary collaboration, and a concentrated effort to make construction workplaces safer, healthier, and more efficient.